2016
DOI: 10.1186/s12936-016-1174-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges with implementing malaria rapid diagnostic tests at primary care facilities in a Ghanaian district: a qualitative study

Abstract: BackgroundRapid diagnostic Tests (RDTs) for malaria enable diagnostic testing at primary care facilities in resource-limited settings, where weak infrastructure limits the use of microscopy. In 2010, Ghana adopted a test-before-treat guideline for malaria, with RDT use promoted to facilitate diagnosis. Yet healthcare practitioners still treat febrile patients without testing, or despite negative malaria test results. Few studies have explored RDT implementation beyond the notions of provider or patient accepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 40 publications
1
62
0
Order By: Relevance
“…We found important gaps in treatment practices as well—with about two out of three malaria cases being incorrectly managed, much of it due to substantial delays in treatment. Evidence so far shows that this may be due to inadequate guideline emphasis22 or simply lack of knowledge among providers regarding malaria case management 23. In our study countries, we found that undertreatment (26%), specifically monotherapy, was higher than overtreatment (9%) of malaria cases, but both lead to unnecessary wastes in the health system.…”
Section: Discussionmentioning
confidence: 61%
“…We found important gaps in treatment practices as well—with about two out of three malaria cases being incorrectly managed, much of it due to substantial delays in treatment. Evidence so far shows that this may be due to inadequate guideline emphasis22 or simply lack of knowledge among providers regarding malaria case management 23. In our study countries, we found that undertreatment (26%), specifically monotherapy, was higher than overtreatment (9%) of malaria cases, but both lead to unnecessary wastes in the health system.…”
Section: Discussionmentioning
confidence: 61%
“…where health care providers in hospitals and larger health centres preferred making diagnosis of malaria through microscopy [19]. This study revealed that more medical doctors in the Internal Medicine Department (43.3%) made diagnosis of malaria by using clinical symptoms than doctors in any other department.…”
Section: Discussionmentioning
confidence: 85%
“…The health system challenge of perennial shortages of mRDT and other commodities needs to be fixed. [50][51][52] Government-or donor-supported interventions aimed at addressing similar challenges often involve free supply of such commodities. Such interventions are difficult to sustain in the midst of competing health needs and are stopped when funds are depleted.…”
Section: Discussionmentioning
confidence: 99%